Pengaruh Pemberian Ekstrak Daun Kelor (Moringa oleifera) dan Sambiloto (Andrographis paniculata) terhadap Income Over Feed Cost Ayam Broiler - Astuti, Puji; Suripta, Heru (Department of Agribusiness, Halu Oleo University, 2021)
The purpose of this study is to determine the effect of giving kelor (Moringa oleifera) leaf and Sambiloto (Andrographis paniculata) extracts on income over the feed cost of broiler chickens. The material used is 60 DOC (day old chicken) strain ross on average initial weight 93.7 g/head. The study was designed using a completely randomized design (CRD) with four treatments and three replications, and each treatment using the five chickens. The treatment consisted of feeding 5 ml/liter of Moringa leaf and Sambiloto extract, T0: control treatment, T1: bitter extract, T2: Moringa and bitter extract (1:1), T3: Moringa extract. The parameters observed were fed consumption, drinking water consumption, feed conversion ratio, feed cost per gain, and income per feed cost. Feed cost per gain and income per feed cost were analyzed descriptively. The result showed that drinking water consumption ((196,18-209,07 ml/head/day) was not significantly different. The lowest feed consumption (85,32 g/head/day) and feed conversion (1,34) were found in the treatment of Moringa extracts. The lowest feed cost per gain (Rp/kg) was the treatment with Moringa leaf extract, the highest income over feed cost (Rp. 9.358,84/kg) was the administration of Moringa extract. It can be concluded that Moringa leaf extract gave the best results on feed consumption, feed conversion ratio, feed cost per gain, and income over feed cost.